Patient Perspectives: Atopic dermatitis (eczema). Issue 1 (January 2016) - Unknown
Abstract : With the now‐universal access to web‐based information, there is a need to provide clear, concise, and accurate medical information to patients and their families informing them about their medical conditions. Most practioners rely on electronic health records, and the ability to share information with patients in the form of "patients handouts" is easier than ever. Pediatric dermatologists, dermatologists, pediatricians, family practitioners, and internists diagnose a number of conditions in common and the SPD has initiated work on a patient handout database (found athttp://pedsderm.net ), aimed at disseminating reliable information to be used by these provider communities. The SPD will be publishing a new handout in each issue of Pediatric Dermatology .